CFD and CAA analysis of single stream isothermal jets with noise suppression devices. - Bernardo Santos Aflalo (2009)
Since the 50's, with the appearance of the turbojet engines, the jet noise is being exhaustively studied, because it is one of the most important source of aircraft noise. Many attempts have been made to reduce the jet noise, including higher by-pass turbofan engines. Chevron nozzles also have been used by the industry to try to reduce the jet noise with a low performance and weight penalty. This work shows a computation procedure to assess how this noise suppression devices impact on both fluid dynamics and acoustics of single isothermal jets. Towards this goal, different chevron nozzles, with 6, 8 and 12 lobes have been analyzed. The calculation procedure is based on a Reynolds Average Navier-Stokes calculation, followed by a stochastic noise generation and radiation method, resulting in a relatively fast noise calculation procedure. The simulations have been carried out using the commercial software CFD++. The calculation procedure has predicted the expected fluid dynamic and acoustic behavior for chevron nozzles, e.g., shortening the potential core length, high frequency noise increase and low frequency noise attenuation. The parametric study of the number of lobes has shown that this parameter impacts the mixing region. Moreover, varying this parameter is a way to attain different low frequency reductions, without great impacts on the highest frequencies. Although the procedure did not capture correctly the absolute values of the acoustic response, the results show that this relatively simple and quick analysis reproduced important parameters in designing new nozzles and can be used as a way to better understand the influence of chevrons.